English Grammar : (Video Aided Instruction, 2004)
Video Aided Instruction's English Grammar Series makes the tricky rules of English grammar easier to learn than ever before - whether you're new to English or you've been speaking it for years! Perfect for classroom use or self-study, this program uses easy-to-follow examples and practice exercises from everyday life to help you master even the most complicated English grammar topics! It's also great for reviewing forgotten grammar or preparing for many verbal standardized exams such as the SAT, TOEFL, GED, and GRE. Plus, it can really help you improve your grades in school or advance your career! To communicate effectively, you must understand the different roles that words play in your sentences. The parts of speech - verbs, nouns, pronouns, adjectives, adverbs, prepositions, conjunctions, articles, and interjections - are the very building blocks of the English language. Lots of folks find these labels confusing - this program will help you make sense of them! So don't let mistakes in English grammar embarrass you - now you can eliminate them from your speaking and writing forever.